Periodontal Stem Cells- The Regeneration Front - J, Vishnusripriya; M. R, Arjun; Raj, Mahesh; Deenadayalan, M.; K. M, Dayakrishna (International Journal Of Drug Research And Dental Science, 2022)
The ultimate goal of periodontal regeneration is to restore the damaged alveolar bone proper, root cementum, and periodontal ligament with collagen fibers inserted into the root surface. The search for new regenerative strategies is a challenging field of periodontal research, and tissue engineering, using stem cells, has recently been shown as a promising approach. Periodontal tissue stem cells, which play a crucial role in maintaining the homeostasis of periodontal tissues, are found in the periodontal ligament (PDL). These cells have long been referred to as mesenchymal stem/stromal cells (MSCs), and their clinical applications have been extensively studied. However, tissue stem cells in the PDL have not been thoroughly investigated, and they may be different from MSCs. Recent advances in stem cell biology, such as genetic lineage tracing, identification of label-retaining cells, and single-cell transcriptome analysis, have made it possible to analyze tissue stem cells in the PDL in vivo. In this review, we summarize recent findings on these stem cell populations in PDL and discuss future research directions toward developing periodontal regenerative therapy.